Lane Changing Nature Of The Driver Amidst Busy Roads In The Country - et. al., Shalini Yadav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Lane changing behavior is the subject being studied since the very beginning when transportation research started. From classical transportation problem to the new era of autonomous driving, lane change behavior has helped the intelligent transportation system great heights. The basic lane change behaviors of drivers on the road has helped in modelling complex traffic situations. This paper studies how many times the driver changes lane in different situations. A number of parameters are considered and the results are analyzed in tabular format. The time of day, location, type of road, mood of driver, type of vehicle, vehicular density, etc are considered. The spatial and temporal parameters are considered. The effect of lane change on local traffic is recorded.